The influence of micro-scale thermal habitat on the movements of juvenile white sharks in their Southern California aggregation sites - Spurgeon, Emily; Thompson, Marten L.; Alexander, Mitchell D.; Anderson, James M.; Rex, Patrick T.; Stirling, Brian; Abbott, Kevin; Lowe, Christopher G. (Frontiers in Marine Science, 2024)
While juvenile white sharks (JWS) can display regional endothermy, the need to maintain internal temperatures within an energetically favorable range likely drives thermoregulatory movements to maximize growth and foraging efficiency. Many JWS from the northeastern Pacific population aggregate seasonally in nearshore nursery habitats throughout the Southern California Bight and historic data show that inter-seasonal movement patterns may be heavily dependent on ambient water temperature. However, the degree to which micro-scale (e.g., 10 m2) water temperature heterogeneity influences JWS three-dimensional movement within nearshore aggregation sites is unknown. High-resolution temperature and passive acoustic-telemetry geo-positional data were used to quantify how temperature and vertical thermal stratification influenced JWS movement using several modeling approaches. JWS selected for water temperatures between 16 – 22°C and depths shallower than 2 m. Sharks occupied deeper waters during dawn and dusk periods, and their distance from the seafloor and spatial orientation of their depth distribution was significantly related to the thermal structure of the water column across the monitored area. Tagged sharks remained above a 16°C thermal threshold and altered their horizontal and vertical distributions accordingly. While high-resolution movement and environmental data provide improved predictability of micro-scale habitat use and distribution, other variables such as prey distribution, behavior, and competition would further improve habitat use models for this highly mobile species.